Między dźwiękiem, słowem i obrazem: o przestrzenności w muzyce - Płaczek, Katarzyna (Investigationes Linguisticae, 2018)
The aim of this paper is to analyse the role of space in the imagination of music listeners. It includes general observations on the place and the importance of the problem of space in musical studies and it explores the peculiarity of some aspects of the music reception. Furthermore, it focuses on the relationship between literature and 19th century programme music in order to point different techniques used by composers to produce spatial associations in listeners’ imagination.